Diminished quality of life among adolescents with coeliac disease using maladaptive eating behaviours to manage a gluten‐free diet: a cross‐sectional, mixed‐methods study. Issue 3 (5th March 2019) - Cadenhead, J. W.; Wolf, R. L.; Lebwohl, B.; Lee, A. R.; Zybert, P.; Reilly, N. R.; Schebendach, J.; Satherley, R.; Green, P. H. R.
Abstract: Background: Certain approaches to managing a strict gluten‐free diet (GFD) for coeliac disease (CD) may lead to impaired psychosocial well‐being, a diminished quality of life (QOL) and disordered eating. The present study aimed to understand adolescents' approaches to managing a GFD and the association with QOL. Methods: Thirty adolescents with CD (13–17 years old) following the GFD for at least 1 year completed the Celiac Dietary Adherence Test (CDAT) and QOL survey. Their approaches to GFD management were explored using a semi‐structured interview, where key themes were developed using an iterative process, and further analysed using a psychosocial rubric to classify management strategies and QOL. CDAT ratings were compared across groups. Results: Gluten‐free diet management strategies were classified on a four‐point scale. Adaptive eating behaviours were characterised by greater flexibility (versus rigidity), trust (versus avoidance), confidence (versus controlling behaviour) and awareness (versus preoccupation) with respect to maintaining a GFD. Approximately half the sample (53.3%) expressed more maladaptive approaches to maintaining a GFD and those who did so were older with lower CD‐Specific Pediatric Quality of Life (CDPQOL) scores, mean subscale differences ranging from 15.0 points for Isolation ( t =  2.4, P =  0.03, d.f. = 28) to 23.4 points for Limitations ( t =  3.0, P =  0.01, d.f. = 28). Conclusions: Adolescents with CD who manage a GFD with maladaptive eating behaviours similar to known risk factors for feeding and eating disorders experience diminished QOL. In accordance with CD management recommendations, we recommend ongoing follow‐up with gastroenterologists and dietitians and psychosocial support referrals, as needed.